Development of a Reverse-Phase Hplc Method for the Quantification of Cryptolepine in the Dry Roots of Cryptolepis Sanguinolenta - Ofori, Edward (2011)
A Thesis Submitted In Partial Fulfilment Of The Requirements for the Degree Of Master of Science In Pharmaceutical Analysis and Quality Control.